The lost world - Hoyt, Harry O., 1880-1961; Beery, Wallace; Doyle, Arthur Conan, 1859-1930.; First National Pictures, Inc.; Cinetel Films ([United States] : First National Pictures, Inc., 1925)
Professor Challenger, the man of vision who persuades his skeptical colleagues to return with him to a remote South American plateau where he has discovered living dinosaurs. Resisting danger and death, Challenger's party return to London in triumph with a captive Brontosaurus. But the beast excapes, turning the city into a shambles and standing the 20th century on it's head.
Based on the novel: The lost world / Sir Arthur Conan Doyle.
Wallace Beery, Bessie Love, Lewis Stone, Lloyd Hughes, Alma Bennett, Arthur Hoyt, Margaret McWade, Bull Montana, Finch Smiles, Jules Cowles, George Bunny, Charles Wellsley, Jocko.
Cinematographer, Arthur Edeson; editor, George McGuire.
Silent, with English intertitles and musical accompaniment; optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Challenger, Professor (Fictitious character) -- Drama; South America -- Drama; Prehistoric peoples -- Drama; Dinosaurs -- Drama; Science fiction films; Animated films; Feature films; Film adaptations; Silent films; Internet videos; Streaming video